Development of smart talking plant with voice recognition function - Zaragoza, Mechelle Grace; Kim, Haeng Kon; Hwang, Ha Jin * (International Association of Engineers, 2017)
Plants can tell us what is affecting them with the electrical signals they emit with the help of (Internet of things) IoT.In such ways that is your plant thriving under current light levels? Is your plant thirsty? Or even satisfy with your care? The goal this project is to encourage a happy relationship between plants and people as a lot of people are afraid of plants. Not they are not green handed. The idea of taking good care is a responsibility. This makes it possible for them to have a plant in their lives. As Arduino came into the picture in bringing a better solution for plant care, we proposed an ideal smart plant based on an existing system that will add more features to it to make an all in one architecture. We also presented some useful projects related to this for comparison and future references.